2021
DOI: 10.1111/jocn.15978
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ views of using virtual reality in healthcare: A qualitative study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 56 publications
4
44
0
Order By: Relevance
“…The literature suggests that AI technologies can support compassion by helping health professionals to understand and respond to human suffering. Specific examples include immersive VR training on psychological symptoms of dementia ( Jones et al, 2021 ); VR training using vignettes for Parkinson’s disease ( Hess et al, 2022 ), and VR training for testicular disease ( Saab et al, 2022 ). However, benefits of student engagement and perceived learning associated with immersive learning may not translate into better exam scores or clinical skills ( Jacobs and Maidwell-Smith, 2022 ) without sufficient preparation or teaching support ( Saab et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature suggests that AI technologies can support compassion by helping health professionals to understand and respond to human suffering. Specific examples include immersive VR training on psychological symptoms of dementia ( Jones et al, 2021 ); VR training using vignettes for Parkinson’s disease ( Hess et al, 2022 ), and VR training for testicular disease ( Saab et al, 2022 ). However, benefits of student engagement and perceived learning associated with immersive learning may not translate into better exam scores or clinical skills ( Jacobs and Maidwell-Smith, 2022 ) without sufficient preparation or teaching support ( Saab et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear how to maintain the initial benefits and permanence of behavior change produced by shortterm virtual health coaching interventions (Bevilacqua et al, 2020) and this needs further research to attain lasting clinical benefits. Findings in the literature suggests there is great potential for AI technologies to enhance underexplored elements of compassion by enriching education, learning and clinical practice (Sukhera and Poleksic, 2021;Saab et al, 2022). There appears to be an "engagement factor" (Navarrete et al, 2021) associated with immersive VR environments which could be further explored for student engagement and empathy awareness as well as other elements of compassion, such as making a judgment about the suffering (the need to 10.3389/fpsyg.2022.971044 act).…”
Section: Safety and Clinical Effectiveness Of Ai Technologies (4 Arti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of willingness to serve older adults [ 10 , 13 , 17 , 24 , 32 , 33 ] have reported that through learning to interact with older adults, nursing students can observe older adults’ verbal and nonverbal cues, with such interaction increasing their willingness to serve and care for older adults. This study used VR learning materials, and the results revealed that through the VR simulation scenario, the opportunities for students to interact with older adults were increased.…”
Section: Discussionmentioning
confidence: 99%
“…in buyer-supplier relations; Boyd and Koles, 2019) or the training of employees (e.g. communication with patients; Saab et al. , 2022).…”
Section: Ar- and Vr-enhanced Service Communicationmentioning
confidence: 99%